PENGUJIAN THREE-POINT BENDING PADA KOMPOSIT SANDWICH KAYU BALSA DAN FIBERGLASS UNTUK RANCANG BANGUN PESAWAT GLIDER - Rahmah, Annisa
The purpose of this research is to analyse bending strength of composite structure that was made of balsa wood as its core and fiberglass woven roving WR200 as its face. Balsa wood was chosen as the core because of its high strength-to-weight ratio. This research went through several steps as research method. First, literature review was conducted by reading journals and books related with the chosen topic. The next step is the making of specimens and quality control of each of them. Each specimen underwent three-point bending test and the data was collected. The data that had been collected from the test was then analysed. Lastly, the conclusion and recommendation were generated based on the findings from the data. The two specimens which were tested by three-point bending test in this research are sandwich composite with vertically aligned balsa wood as its core (core perpendicular to the length of specimen) and sandwich composite with horizontally aligned balsa wood as its core (core aligned with the length of specimen). Sandwich composite with horizontally aligned core has the maximum load of 697.2 N, while the value of maximum core shear strength and face bending strength are 0.768 MPa and 37.171 MPa. Sandwich composite with vertically aligned core has the maximum load of 1098.5 N, while the value of maximum core shear strength and face bending strength are 1.208 MPa and 67.113 MPa. According to the test result of the two kinds of specimens, sandwich composites with vertically aligned core are stronger than horizontally aligned core ones. This research is limited to fiberglass woven roving WR200 with the degree of orientation in the value of ±45° as the face. The specimens are made in Kebon Cabe, Tangerang Selatan.